"Le passeport de la douleur ou rien": Fawzia Zouari's Ce pays dont je meurs and the politics of pain. Issue 1 (April 2015) - Kemp, Anna
Abstract : French-Maghrebi literature is often seen to be complicit in what Madeleine Hron calls a "politics of pain" whereby the writer displays the suffering of her perceived cultural group in a bid for recognition, understanding and compassion. In such readings, the group's suffering is often imagined to be expressed via the protagonist's sick or wounded body. This reading of Fawzia Zourai's novel Ce pays dont je meurs argues, against existing scholarship, that the body of Zouari's anorexic protagonist, though it gives expression to a shared suffering also, paradoxically, articulates a critique of a "politics of pain" and the political potential of empathy that informs it.